Permafrost collapse is accelerating carbon release - Turetsky, Merritt R.; Abbott, Benjamin W.; Jones, Miriam C.; Walter Anthony, Katey; Olefeldt, David; Schuur, Edward A. G.; Koven, Charles; McGuire, A. David; Grosse, Guido; Kuhry, Peter; Hugelius, Gustaf; Lawrence, David M.; et al. (Nature (London), 2019)
The sudden collapse of thawing soils in the Arctic might double the warming from greenhouse gases released from tundra, warn Merritt R. Turetsky and colleagues. The sudden collapse of thawing soils in the Arctic might double the warming from greenhouse gases released from tundra, warn Merritt R. Turetsky and colleagues. Soil erosion due to permafrost thaw in the Batagaika crater in eastern Siberia